Peran Resiko Sanksi Pada Pengaruh Good Governance Dan Whistlebowing System Terhadap Kepatuhan Wajib Pajak - Ningrum, Lutfi Silfia; Trisnaningsih, Sri (Universitas Pendidikan Ganesha, 2021)
Â This study aims to determine the effect of Good Governance and Whistleblowing System on individual taxpayer compliance with Tax Sanctions as a moderating variable in the Pratama Surabaya Mulyorejo Tax Office (KPP). The population in this study were all individual taxpayers registered at KPP Surabaya Mulyorejo. The number of samples used in this study were 100 respondents who were calculated based on the Slovin formula with the incidental sampling method sampling technique. Data collection in this study was carried out by using a questionnaire method. The method used in this research is MRA (Moderate Regression Analysis). The results showed that Good Governance and Whistleblowing System had a positive effect on Taxpayer Compliance. The Tax Sanctions variable can moderate the relationship between Good Governance and the Whistleblowing System on Taxpayer Compliance.